Angle analysis model of pressure-assisted laser forming and high-precision method. (October 2021) - Guo, Yankuo; Shi, Yongjun; Wang, Xiaogang; Li, Xianfa; Chen, Tingting
Highlights: The analytical model of PALF is established, and the error is less than 4.57%. A new method of achieving high precision is proposed. The analytical model and method are beneficial to improve processing efficiency. Abstract: Pressure-assisted laser forming (PALF) is a new research direction based on laser forming. This technology has more advantages in increasing bending angle and controlling bending direction. The establishment of analysis model is great significance to clarify the deformation mechanism and improve the machining efficiency. However, the analysis model of PALF has not been studied. In this paper, the prestress and thermal stress are analyzed respectively, then strain coupling is carried out for both types of stress. Finally, the analytical model is obtained. Experimental results show that the average error of the laser bending angle obtained by the analytical model is less than 4.57% under different pressure and less than 4.11% under different laser power. To further improve the accuracy of the analytical model (the demand for high precision is becoming increasingly urgent in processing and production), a new method of achieving high precision is proposed on the basis of this model. In this method, the model equation is simplified. Then, the precision of this equation is corrected through two experiments. Finally, the high-precision equation is obtained. The results show that the errors are less than 0.73%. Through this high-precision equation, any combination of parameters (pressure, scanning position, plate length, plate width) can achieve any high-precision bending angle.